New Evidence on the Importance of Instruction Time for Student Achievement on International Assessments - Jan Bietenbeck; Matthew Collins (Lund University, School of Economics and Management, Department of Economics, 2020)
We revisit and substantially extend the evidence on the importance of instruction time for student achievement on international assessments. We first successfully replicate the estimate of a positive effect of weekly instruction time in the seminal paper by Lavy (Economic Journal, 125, F397-F424) in a narrow sense. We then extend the analysis to data from other international student assessments and find effects that are consistently smaller in magnitude. We provide suggestive evidence that this divergence is partly due to different measurement of instruction time in the data used in the original paper. Our results suggest that differences in instruction time play a less important role than previously thought for explaining international gaps in student achievement.
Keywords: I21; 330; instruction time; student achievement; PISA; TIMSS